Use of ondansetron to prevent postspinal morphine induced vomiting - Sharma, NR; Shrestha, P (Journal of Institute of Medicine Nepal, 2008)
Background: The use of Ondansetron, a selective serotonin type 3 (5-hydroxytryptamine [5-HT3] antagonists has been used to prevent postspinal morphine induced vomiting in post-surgical cases. Besides this it has been widely used for the prevention of vomiting induced by chemtherapy postanaesthesia and radiotherapy. Methods: A prospective study was carried out for the use of ondansterone to prevent morphine induced post spinal vomiting in vaginal hysterectomy cases at Gaur, Mahottari district in eastern part of Nepal from 02 - 12 - 2006 to 09- 12- 2006. A total of 100 cases were taken in the study. Result: Among the 100 cases of postspinal morphine 15 case (15%) found to have episodes of vomiting,5% cases reported mild pruritus and 10% had complains of pain, but even a single case did not have respiratory depression. Conclusion: Use of Ondansetron can decrease the incidence of nausea and vomiting produced by intrathecal morphine however many studies have revealed no significant difference between the placebo group. Key words: Ondansterone, Morphine, spinal anesthesia, vomiting The full text of this paper is available at Journal of Institute of Medicine website